Isolation of a Novel Caprine Eimeria christenseni Strain (GC) in Canary Islands and Analysis of Parasitological, Clinical, and Pathological Findings on Experimentally Infected Goat Kids - Emilio Barba; José Manuel Molina; Francisco Rodríguez; Otilia Ferrer; María Carmen Muñoz; Liliana M. R. Silva; María Cristina Del Río; José Adrián Molina; Anja Taubert; Carlos Hermosilla; Antonio Ruiz (Animals)
Eimeria christenseni is considered among the most pathogenic Eimeria species in goats. The aim of this study was to isolate an E. christenseni strain and to assess its infectivity, pathogenicity, and ability to develop a protective immune response. After previous collection of E. christenseni-positive faeces, purification of oocysts, and amplification in donor animals, an experimental infection was carried out. A total of 19 kids were divided into three groups: primary-infected and challenged, challenge control, and uninfected control. Infections were performed orally with 2 × 105 sporulated oocysts per animal. Oocyst shedding, clinical signs, and production parameters, in addition to haematological and histopathological features, were monitored. The results showed that the Gran Canaria (GC) E. christenseni strain had similar morphological and biological characteristics to those previously described, but no significant clinical signs were observed despite the high oocyst counts here recorded. The novel strain isolated would therefore be of low pathogenicity but still able to develop significant immunoprotective responses upon challenge infections. Its biological similarities to highly pathogenic species such as Eimeria ninakohlyakimovae and Eimeria arloingi might enable comparative studies aimed at developing alternative strategies for drug treatments, including Eimeria species (strain)-specific vaccination strategies for the efficient control of goat coccidiosis.